THE IMPORTANCE OF GYMNASTIC EXERCISES IN MAINTAINING WOMEN'S HEALTH AND THE PERIOD OF WEEKLY TRAINING (World Bulletin of Public Health, 2024)
In this article, pregnant women of all ages, who are ready for motherhood, plan and apply various changes in the abdominal muscles that remain after the fetus (overweight, skin muscle expansion, muscle relaxation, damaged skin cells) with the help of microcycles.
Keywords: Childbirth; period; skin muscles; gymnastic exercises